P10.06 Stiff limb syndrome associated to anti NMDA-R antibodies. (6th September 2019) - Birzu, C; Jaume, L; Rostomashvilli, S; Honnorat, J; Berzero, G; Psimaras, D
Abstract: BACKGROUND: Stiff person spectrum disorder is a group of rare conditions clinically characterized by the core symptoms of fluctuating muscular stiffness with superimposed spasms and an exaggerated startle response (hyperkplexia). It includes multiple variants amongst which are focal forms like stiff limb syndrome. Up to date, it was described in association with a spectrum of antibodies interfering with gabaergic transmission, most frequently antibodies targeting GAD, glycine receptor, amphiphysin and more rare dipeptidylpeptidase like protein 6, gephyrin, GABAAR and Glycine transporter 2. MATERIAL AND METHODS: We report the case of a stiff limb syndrome associated to anti-NMDAR antibodies. The patient, a French 44-year male, with no antecedents presents with a 2-month history of painful spasms in his both legs resulting in a difficulty of walking and multiple falls. The diagnosis was supported by a stiff limb syndrome clinical pattern, a clinical response to treatment with benzodiazepines and baclofen and by the absence of other neurological finding that could have suggested an alternative diagnosis. RESULTS: Anti NMDA-R antibodies were identified in blood and CSF samples using both immunofluorescence and cell-based assay. Any other intracellular and surface antibodies were negatives, GAD-ab included. Oncological evaluation was negative. The patient didn't present encephalopathy signs and neuropsychological evaluation was normal. The patient received immunotherapy with one cure of intravenous immunoglobulins after an only partial improvement with symptomatic treatment. CONCLUSION: This is the first case report of an association between the anti NMDA-R and stiff limb syndrome. Further investigations are needed to provide a better understanding of the pathophysiology of stiff person spectrum disorders.